PERANAN BADAN KEPEGAWAIAN DAN DIKLAT DAERAH DALAM REKRUITMEN CALON PEGAWAI NEGERI SIPIL DI KABUPATEN POLEWALI MANDAR SULAWESI BARAT - Abd. Khalik (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2016)
This study explains the role of the Regional Personnel Agency in the implementation of the recruitment of prospective Civil Servants (CPNS) in the Scope of the Polewali Mandar District Government, and explains the factors (internal and external) that influence it. The type of research used is qualitative-descriptive which describes the answers to the main problems of the study. Data collection is done using observation and interviews. The collected data was processed and analyzed descriptively qualitatively. The results of the study explained that in the recruitment of candidates for Regional Civil Servants there were still frequent conflicts of interest between various elements both between the organizers and the work units of the institutions associated with the honorary staff appointed to the Regional Candidates of Civil Servants. Factors that influence the implementation of Candidate Recruitment Candidates in Polewali Mandar District are still colored by various levels of interest that affect the effectiveness and smooth implementation of PP. 43 2007.